2022
DOI: 10.1177/02841851221107626
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of intravoxel incoherent motion combined with diffusion kurtosis imaging for breast cancer axillary lymph node metastasis: a retrospective study

Abstract: Background Non-invasive imaging technologies for assessing axillary lymph node (ALN) metastasis of breast cancer are needed in clinical practice. Purpose To explore the clinical value of intravoxel incoherent motion (IVIM) and diffusional kurtosis imaging (DKI) for predicting ALN metastasis of breast cancer. Material and Methods A total of 194 patients with pathologically confirmed breast cancer who underwent IVIM and DKI examination were reviewed retrospectively. The IVIM derived parameters of D, D*, and f an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although our study has been focusing on mean kurtosis imaging in the human brain, it is clear that DKI has wide application outside of the brain (Li et al, 2022b ;Liu et al, 2021 ;Huang et al, 2021a ;Guo et al, 2022a ;Li et al, 2022a ,d;Zhou et al, 2022 ). Without having conducted experiments elsewhere, we cannot provide specific guidelines for mean kurtosis imaging in the breast, kidney, liver, and other human body regions.…”
Section: Kurtosis Estimation Outside Of the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study has been focusing on mean kurtosis imaging in the human brain, it is clear that DKI has wide application outside of the brain (Li et al, 2022b ;Liu et al, 2021 ;Huang et al, 2021a ;Guo et al, 2022a ;Li et al, 2022a ,d;Zhou et al, 2022 ). Without having conducted experiments elsewhere, we cannot provide specific guidelines for mean kurtosis imaging in the breast, kidney, liver, and other human body regions.…”
Section: Kurtosis Estimation Outside Of the Brainmentioning
confidence: 99%
“…Recent clinical benefits of using kurtosis metrics over other DW-MRI derived measures have been demonstrated for grading hepatocellular carcinoma (Li et al, 2022b ), prognosing chronic kidney disease (Liu et al, 2021 ), differentiating parotid gland tumours (Huang et al, 2021a ), measuring response to radiotherapy treatment in bone tumour (Guo et al, 2022a ) and glioblastoma (Goryawala et al, 2022 ), identifying tissue abnormalities in temporal lobe epilepsy patients with sleep disorders (Guo et al, 2022b ) and brain microstructural changes in mild traumatic brain injury (Wang et al, 2022 ), monitoring of renal function and interstitial fibrosis (Li et al, 2022a ), detecting the invasiveness of bladder cancer into muscle (Li et al, 2022d ), aiding management of patients with depression (Maralakunte et al, 2022 ), delineating acute infarcts with prognostic value (Hu et al, 2022 ), predicting breast cancer metastasis (Zhou et al, 2022 ), diagnosing Parkinson's disease (Li et al, 2022c ), amongst others reported prior and not listed here.…”
Section: Introductionmentioning
confidence: 99%
“… 14,19,22 Zhou et al reported borderline higher diagnostic efficiency of DKI compared with conventional MRI ( p = 0.048). 22 …”
Section: Clinical Applicationsmentioning
confidence: 99%